MENINGKATKAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH PEMULA DALAM PENYUSUNAN RENCANA KERJA SEKOLAH MELALUI PEMBINAAN BERKELANJUTAN - SITTI ROSWATI SUJUTI (ACADEMIA: Jurnal Inovasi Riset Akademik, 2022)
The education unit is led by the principal and every activity in the education unit is managed on the basis of the School Work Plan. The education unit is required to prepare a Medium Term Work Plan and an Annual Work Plan which is stated in the School Budget Work Plan, hereinafter referred to as the School Work Plan. Based on the supervisor's observations, it shows that most of the schools in the target schools have not prepared RKS. If there is a school that has made it, it is not yet a sequential unit, and the making of the RKJM, RKT, and RKAS does not start with a self-evaluation. This type of research uses school action research (School Action Research) with research subjects are 4 beginner school principals. In the initial conditions, the average percentage of competency achievement in the preparation of school work plans was only 37.50% with the less category, based on this, action was then taken in cycle 1, namely sustainable development. The result of the average percentage of competency achievement in the preparation of school work plans in cycle 1 is 66.25% with sufficient category, but the increase is still not in accordance with the expected achievement indicators. Based on this, action was taken in cycle 2, namely for school principals who were still sufficient or less able to prepare school work plans given special guidance and increasing the coaching time with an emphasis on the difficulties faced and principals who were able to prepare school work plans were given a more detailed explanation and develop the preparation of school work plans The results of the average percentage of competency achievement in the preparation of school work plans in cycle 2 is 90.41% with a very good category. This means, there is an increase from the initial conditions to cycle 2 of 52.91% which is from the poor category to the very good category. ABSTRAKSatuan pendidikan dipimpin oleh kepala sekolah dan setiap kegiatan di satuan pendidikan dikelola atas dasar Rencana Kerja Sekolah. Satuan pendidikan wajib menyusun Rencana Kerja Jangka Menengah dan Rencana Keja Tahunan yang dinyatakan dalam Rencana Kerja Anggaran Sekolah yang selanjutnnya disebut Rencana Kerja Sekolah. Berdasarkan pengamatan pengawas menunjukkan bahwa sebagian besar sekolah yang berada di sekolah binaan belum menyusun RKS. Jika ada sekolah yang membuat belum merupakan satu kesatuan yang urut, dan pembuatan RKJM, RKT, dan RKASnya tidak diawali dari Evaluasi Diri. Jenis penelitian ini menggunakan penelitian tindakan sekolah (School Action Research) dengan subjek penelitian adalah 4 orang kepala sekolah pemula. Pada kondisi awal prosentase rata rata ketercapaian kompetensi dalam penyusunan rencana kerja sekolah hanya sebesar 37.50% dengan kategori kurang, berdasarkan hal tersebut kemudian dilakukan tindakan pada siklus 1 yaitu pembinaan berkelanjutan. Hasil prosentase rata rata ketercapaian kompetensi dalam penyusunan rencana kerja sekolah pada siklus 1 adalah 66.25% dengan kategori cukup, namun peningkatan tersebut masih belum sesuai dengan indikator ketercapain yang diharapkan. Berdasarkan hal tersebut dilakukan tindakan pada siklus 2 yaitu terhadap kepala sekolah yang masih cukup atau kurang mampu menyusun rencana kerja sekolah diberikan pembinaan khusus dan menambah waktu pembinaannya dengan titik berat pada kesulitan-kesulitan yang dihadapi dan terhadap kepala sekolah yang sudah mampu menyusun rencana kerja sekolah diberi penjelasan lebih rinci dan mengembangkan penyusunan rencana kerja sekolah Adapun hasil prosentase rata rata ketercapaian kompetensi dalam penyusunan rencana kerja sekolah pada siklus 2 adalah 90.41% dengan kategori amat baik. Hal ini berarti, terjadi peningkatan dari kondisi awal sampai dengan siklus 2 adalah sebesar 52,91% yang mana dari kategori kurang menjadi kategori amat baik.